The interplay of tax incentives and global investments in a dynamic economic landscape - Serdinova, A. (My University, 2023)
In the changing scenarios of global economics, the utilization of tax incentives has emerged as a strategic instrument, particularly in the realm of mobile activities. Positioned as potential "beggar-thy-neighbor" tools, tax incentives hold the promise of influencing the global investment landscape. However, the translation of their impact into a substantial surge in worldwide investments is not a foregone conclusion. Instead, a noteworthy outcome could be the relocation of investments across different jurisdictions. This phenomenon prompts a crucial realization that the effectiveness and adoption of tax incentives extend beyond their design parameters.
Keywords: tax incentives; податкові пільги; investment; інвестиція